2014
DOI: 10.1177/1745691614527464
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroscience of Intergroup Relations

Abstract: We review emerging research on the psychological and biological factors that underlie social group formation, cooperation, and conflict in humans. Our aim is to integrate the intergroup neuroscience literature with classic theories of group processes and intergroup relations in an effort to move beyond merely describing the effects of specific social out-groups on the brain and behavior. Instead, we emphasize the underlying psychological processes that govern intergroup interactions more generally: forming and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
235
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 281 publications
(257 citation statements)
references
References 288 publications
(407 reference statements)
10
235
1
Order By: Relevance
“…Recent research in social neuroscience has investigated other brain areas involved in empathy, and have reported findings clearly establishing neural activity associated with intergroup bias [42,43]. One key study [44], for example, involved Chinese and Caucasian A c c e p t e d M a n u s c r i p t activations in the dorsal anterior cingulate cortex and anterior insula cortex (two regions typically activated during the experience of pain) in participants, whereas this response was diminished when viewing faces of the outgroup race.…”
Section: How Does the Brain Produce Intergroup Empathy?mentioning
confidence: 99%
“…Recent research in social neuroscience has investigated other brain areas involved in empathy, and have reported findings clearly establishing neural activity associated with intergroup bias [42,43]. One key study [44], for example, involved Chinese and Caucasian A c c e p t e d M a n u s c r i p t activations in the dorsal anterior cingulate cortex and anterior insula cortex (two regions typically activated during the experience of pain) in participants, whereas this response was diminished when viewing faces of the outgroup race.…”
Section: How Does the Brain Produce Intergroup Empathy?mentioning
confidence: 99%
“…Whilst the design of this experiment was not optimized to look at how the brain processes the rewards received by others, the ACCg did respond differently to ingroup individuals compared to others. Notably, this is a distinct region of the ACC from that engaged when processing the similarity of others (Cikara & Van Bavel, 2014; Losin, Cross, Iacoboni, & Dapretto, 2014). This suggests that the response of ACCg to rewards that others will receive may depend on their group membership.…”
Section: Discussionmentioning
confidence: 98%
“…Recent meta‐analyses have highlighted that the DMPFC and the Insula are key regions that respond differentially to equitable and inequitable offers in the UG (Feng et al., 2015; Gabay et al., 2014). Similarly, a large number of different paradigms have shown that several regions including both the DMPFC and VMPFC respond to ingroup and outgroup members differently (Cikara & Van Bavel, 2014; Cikara et al., 2014; Harris & Fiske, 2006; Hein et al., 2010; Molenberghs et al., 2016). The response in these regions has been shown to predict helping of outgroup members and differential punishment of ingroup versus outgroup behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations